Periodontal Disease and Potential Association with Systemic Diseases and Conditions (Mini-review) - S. Elburki, Muna (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Periodontitis, the most common chronic inflammatory disease known world-wide, is characterized by pathologically-excessive degradation of collagen and other connective tissue constituents and accelerated resorption of the alveolar bone in the periodontal supporting structures of the teeth including the gingiva, periodontal ligament and the alveolar bone. Nationwide, the prevalence of periodontal disease, in some form, is known to affect up to 50% of the adult population and is a substantial inflammatory burden which can be detrimental to over-all systemic health. In this regard, this common dental disease, chronic periodontitis, has, over the past few decades, been increasingly linked to a variety of medical diseases such as cardiovascular disease (CVD) and stroke, increased severity of diabetes, low birth weight babies (controversial), bacterial pneumonia, rheumatoid arthritis, osteoporosis, Crohn’s disease, HIV Diseases, and head and neck cancer. Decades ago it was thought that all adults were essentially equally susceptible to periodontal disease. More recently, various risk factors such as genetic factors have been identified which significantly impact the susceptibility to periodontitis. Therefore, identifying individuals at risk for development of severe periodontitis provides a way for early interventions.
Keywords: periodontitis